On the development of the codematic theory of foreign-language learning - Szczodrowski, Marian (Glottodidactica, 2021)
The discussion addresses the linguistic code and its contribution to the development of the codematic theory of foreign-language teaching. This theory deals with the essence and properties of the course of processes of coding and decoding foreign-language structures. Teachers and learners participate in these processes as primary and secondary senders and receivers of transmitted lexical-grammatical structures with the aim of learners’ mastering them. The process of learning and mastering foreign-language structures takes place in two stages, that is, during their decoding and construction in the form of structural matrices in the receiver’s appropriate memory. In this way, in the receiver (learner) there forms a warehousing mechanism with regard to the foreign language. This mechanism is equipped with a receptive and (re)productive functioning force, that is a force that activates the structural matrices. Structural matrices in long-term memory attain the appropriate force of activation, and therefore demand constantly being brought up to date in various syntagmatic-syntactic constructions, that is in the process of their encoding.